Immunosuppressive mechanisms in myeloid cells - Gabrilovich, Dmitry (Henry Stewart Talks, 2014)
Myeloid derived suppressor cells (MDSC) and their potent immune suppressive activity, MDSC in cancer, MDSC in chronic infections, MDSC during stress, MDSC in surgical trauma, The two main populations of MDSC: monocytic MDSC (M-MDSC) and polymorphonuclear MDSC (PMN-MDSC), Biological differences between MDSC and their normal counterparts, Multiple mechanisms of expansion regulation and immune suppressive function of MDSC, MDSC role in antigen-specific T cell tolerance in tumor-bearing mice, Therapeutic regulation of MDSC in mice and humans
Archived at 2024/02/29